Observation Method in the Control of Stacker Capacity Under Landslide Hazard – A Case Study - Bąk Miłosz; Bagińska Irena (Studia Geotechnica et Mechanica, 2022)
The article presents both an application and the purpose of the observation method in the control of stacker capacity. It lists the types of the measured (observed) quantities, which serve as a basis for the observation method. It also describes the procedure of the method and discusses its individual steps. It further provides examples of applying the method in defining the capacity levels of a stacking machine ZGOT-11500, based on the recorded surface and subsurface soil displacement values. The article also offers the increment values and speeds for the individual parameters, which serve as a warning against deterioration of the geotechnical condition of the soil. Knowledge of the relationships between the parameters that describe soil deformation and the required defined stacker capacity may serve as a basis for further research and experiments on the observation method, which may increase the safety of stacking operations. The analysis was based on the results of geotechnical and geodetic measurements, as well as on the operating parameters of the stacker, acquired over a period of 5 months.